PENGARUH STRATEGI PENYULUHAN DAN TINGKAT PENDIDIKAN TERHADAP KEPEDULIAN KESEHATAN LINGKUNGAN - Pratomo, Suko (Universitas Pendidikan Indonesia, 2015)
The Objective of the research is to study the effect of the extension strategy, the educational level and the interaction effect of those two variables to concern on the environmental health. The research was conducted in Purwakarta Regency with a sample of 36 housewives by using an experiment with analysis technique was used ANAVA with 2 lines; 2x2 factorial design, significantly α: 0,05. Based on the results of these research are: 1) Basically we could find the influence towards the housewives concern on the environmental health of using the cooperative extension strategy and the presentation strategy. 2) The housewives who have high educational level more highly concern towards the environmental health than of those who received presentation. 3) The housewives who have low educational level and received presentation strategy more highly concern towards the environmental health than of those who received cooperative strategy. 4) There is an interaction between extension strategy and the educational level towards the housewives concern on the environmental health.